Genetic testing - Roopa Bijja (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2019)
Genetic testing helps in identifying small changes in the genetic sequence and in turn provides us information about our genome and our body. Types of genetic tests has been expanding over the years. In the past, genetic tests mainly searched for abnormal chromosomes and mutations leading to rare, inherited disorders.